Knowledge and anticipated behavior of health care workers in response to an outbreak of pandemic influenza in Georgia - Maia Butsashvili; Wayne Triner; George Kamkamidze; Maia Kajaia; Louise-Anne McNutt (Journal of Infection in Developing Countries)
Background: Avian influenza has been documented in over 331 humans since 2003 with 203 associated deaths. Health Care Workers (HCWs) have been shown to be at personal risk during other highly virulent outbreaks with a high attack rate. This study aimed to determine the magnitude and factors associated with absenteeism of hospital based health care workers (HCWs) in Georgia associated with a potential highly virulent influenza pandemic. Methodology: This was a cross-sectional study of how HCWs responded to a potentially highly virulent influenza pandemic in two urban hospitals in Georgia. Hospital based physicians and nurses were studied. Data was collected utilizing a survey instrument. The survey was either self-administered or interviewer administered based upon the preference of the respondent. Results: There were 288 HCWs surveyed. The study suggested a 23% rate of worker absenteeism, predominately among women and nurses. The majority of the respondents (58.1%), mostly HCWs less than age 35, were opposed to forced isolation or quarantine of staff during a highly virulent influenza pandemic. Seventy-six percent of respondents correctly reported that the strain of virus that was responsible for the outbreaks in the neighboring countries was H5N1. Only 15.5% of respondents, however, correctly identified influenza as the culprit virus. Conclusions: The rate of work absenteeism suggested by this study represents a significant workforce reduction. There are specific groups who would choose not to attend work in the face of a flu pandemic. This information may allow planners to target these specific groups for education and social support services to encourage greater inclination to attend to clinical duties.